2021
DOI: 10.3390/ijerph18158084
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Promoting Resilience to HIV/AIDS: A Qualitative Study on the Lived Experiences of HIV-Positive, Racial and Ethnic Minority, Middle-Aged and Older Men Who Have Sex with Men from Ontario, Canada

Abstract: Evidence-based research has highlighted the need for exploring factors that support the mental health of men who have sex with men living with HIV/AIDS (MSMLWH), and environmental influences that promote their resilience to HIV/AIDS. This exploratory study utilized a community-based participatory research approach to investigate barriers and facilitators to promoting resilience to HIV/AIDS, specifically among racial and ethnic minority, middle-aged and older MSMLWH, a population that continues to be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
0
10
0
1
Order By: Relevance
“…In the case of TMSM, this reliance on and great appreciation of social engagement, social support, and accessible community resources were distinctly exemplified by the experiences and sentiments described in all three case studies. Several research studies have emphasized the benefits gained by MSM and trans individuals from having perceived social support from LGBTQIA+ friends [ 65 , 66 , 67 , 68 , 69 ], and strong connections with gender-affirming communities and sexual health care [ 46 , 47 , 51 , 52 , 53 , 65 ], especially those that prioritize the elimination of cisgenderism and transphobia [ 70 ]. They have also emphasized the need for such HIV services and programs to create sustainable opportunities to increase the financial security of TMSM, as well as develop more opportunities for TMSM to receive gender affirmation and social support from accessible community resources.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of TMSM, this reliance on and great appreciation of social engagement, social support, and accessible community resources were distinctly exemplified by the experiences and sentiments described in all three case studies. Several research studies have emphasized the benefits gained by MSM and trans individuals from having perceived social support from LGBTQIA+ friends [ 65 , 66 , 67 , 68 , 69 ], and strong connections with gender-affirming communities and sexual health care [ 46 , 47 , 51 , 52 , 53 , 65 ], especially those that prioritize the elimination of cisgenderism and transphobia [ 70 ]. They have also emphasized the need for such HIV services and programs to create sustainable opportunities to increase the financial security of TMSM, as well as develop more opportunities for TMSM to receive gender affirmation and social support from accessible community resources.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored and discussed a variety of factors that have either prospectively served as facilitators to the promotion of resilience to HIV/AIDS among MSM living with HIV/AIDS, or as barriers and challenges to such resilience-building [20,[28][29][30][31]. Examples of facilitators that have been explored include individual characteristics such as perseverance [30,31]; external protective factors such as social support from family and friends, religion and spirituality, and education [16,20,26]; and community-level resources such as lesbian, gay, bisexual, trans, queer, and intersex (LGBTQI+) not-for-profit agencies and AIDS services organizations [17,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored and discussed a variety of factors that have either prospectively served as facilitators to the promotion of resilience to HIV/AIDS among MSM living with HIV/AIDS, or as barriers and challenges to such resilience-building [20,[28][29][30][31]. Examples of facilitators that have been explored include individual characteristics such as perseverance [30,31]; external protective factors such as social support from family and friends, religion and spirituality, and education [16,20,26]; and community-level resources such as lesbian, gay, bisexual, trans, queer, and intersex (LGBTQI+) not-for-profit agencies and AIDS services organizations [17,[32][33][34]. Examples of challenges that have been examined in the research include HIV stigma and discrimination (i.e., negative attitudes toward HIV/AIDS and the negative treatment of PLWH that have been found to exacerbate social isolation and other co-occurring psychosocial health problems) [17,20,24,30,31,35], cultural and language barriers, and racism [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it should be considered that studies indicate that MSM who are older often fail to recognize their susceptibility to HIV and other STIs, leading to inadequate uptake of prevention methods (Hawkinson et al, 2023;Liboro et al, 2021;Queiroz et al, 2023;Roberson, 2018). Research conducted in Brazil has shown high rates of inconsistent condom use in this population, highlighting an urgent need to provide additional prevention measures (Queiroz, Sousa, et al, 2019;Queiroz et al, 2023;Serra et al, 2013;Sousa et al, 2019).…”
mentioning
confidence: 99%